Perancangan Aplikasi Sistem Informasi Stock Barang Masuk Dan Barang Keluar Menggunakan Metode FIFO PT Shaftindo Pratama - Afrina; S.Kom; M. SI; Al Rusman; S.T.; M.Kom; Bagus Susanto Pratama. (Jurnal Teknik Ibnu Sina, 2023)
Along with the development of technology in the era of globalization, the resulting information can be obtained quickly. Technology is also a tool that we use every day to carry out activities, not only in daily life at work also requires information technology that can facilitate work activities so that as a businessman can compete with other business people, applications and information systems are also part of technology which must be very considered in the world of work because this can cut time in work this is very effective compared to manual work without using technology. From the results of interviews that have been conducted According to Mr. Rudi Purnomo as the manager of PT. Shaftindo Pratama in the entry and exit of goods and managing stock of goods, has not been well integrated because there is no information system that helps PT. Shaftindo Pratama in carrying out its business. This has resulted in each part of the data collection not being well documented because it is in the form of files that are input manually through the Microsoft Excel application. To overcome this it is necessary to design an information system to assist the process of managing stock management data. The information system needed is a system that is able to search, add, delete, update, stock data of goods and is able to reduce the number of 1 Perancangan Aplikasi Sistem Informasi Stock Barang Masuk April 2020 | Vol. 5 | No. 1 | Dan Barang Keluar Menggunakan Metode FIFO PT Shaftindo Pratama